Asia Pacific Oil and Gas Conference &Amp; Exhibition 2009
DOI: 10.2118/123473-ms
|View full text |Cite
|
Sign up to set email alerts
|

Wellbore Stability Study: Lessons and Learnings From a Tectonically Active Field

Abstract: Shales account for 75% of the formations drilled worldwide, while drilling troubles associated with shale represents 90% of wellbore stability problems reported. In this paper, a traditional wellbore stability study has been implemented at an onshore gas field in a tectonically active region. Despite following the program however, the drilling experienced significant challenges, particularly in the shales where the sonic logs have shown high velocity and therefore high rock strength. To investigate the root ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Waragai et al [19] inferred that the guideline works, and wellbore instability problems could be mitigated by following it. Han et al [20] showed that a combination of tectonic movements and inappropriate MWW cause fractures on shale formation in the Phu Horm field and, therefore, the wellbore instability issue. As a suggestion, the drilling strategy can be modified while applying proper components and inhibitors to prevent the intrusion of drilling mud [21] into the fractures of underground formations.…”
Section: Numerical Modeling Of Wellbore Stabilitymentioning
confidence: 99%
“…Waragai et al [19] inferred that the guideline works, and wellbore instability problems could be mitigated by following it. Han et al [20] showed that a combination of tectonic movements and inappropriate MWW cause fractures on shale formation in the Phu Horm field and, therefore, the wellbore instability issue. As a suggestion, the drilling strategy can be modified while applying proper components and inhibitors to prevent the intrusion of drilling mud [21] into the fractures of underground formations.…”
Section: Numerical Modeling Of Wellbore Stabilitymentioning
confidence: 99%
“…According to literature, 90% of all well stability problems occur when drilling through shales, formations that account for 75% of all formations through which a well is drilled [8,[26][27][28][29]. The contact of shale with water from mud can cause shale hydration, changing the volume of the rock and reducing its cohesive strength.…”
Section: Introductionmentioning
confidence: 99%